On Developing an Inter-Agency Trust Scale for Assessing Governance Networks in the Public Sector. Issue 4 (8th August 2019) - Song, Andrew M.; Saavedra Cisneros, Angel; Temby, Owen; Sandall, Jean; Cooksey, Ray W.; Hickey, Gordon M.
ABSTRACT: This article presents the development and validation of a psychometric scale for assessing public sector inter-agency trust. The instrument is grounded in contemporary trust theory and methodologically adapted from a measure developed for private sector alliances. Tested using four discrete studies of governance networks, each addressing transboundary environmental issues such as climate change and fisheries, the scale exhibits reasonably valid psychometric properties while also enabling visualized analysis of networked trust distributions. Based on this work, we outline further research needs with a view to stimulating greater trust research in governance networks and facilitating more collaborative and innovative policy outcomes in the public sector.